Doxycycline failure in lymphogranuloma venereum. Issue 4 (26th July 2010) - Méchaï, Frédéric; de Barbeyrac, Bertille; Aoun, Olivier; Mérens, Audrey; Imbert, Patrick; Rapp, Christophe
Abstract : Lymphogranuloma venereum (LGV) cases are currently re-emerging in the homosexual community, particularly in HIV-seropositive patients. The standard treatment for this infection, which is caused by Chlamydia trachomatis L1, L2 and L3 serotypes, is a 3-week doxycycline regimen. The case is reported of a male patient presenting with LGV, who was rapidly cured with moxifloxacin treatment after failure of extended treatment with cyclines. This fluoroquinolone is known to be highly active in vitro on the LGV pathogenic agent. Thus it may be a useful alternative when doxycycline treatment results in failure.